Photoreduction of mercuric bromides in polar ice - Javier Carmona-García; Alfonso Saiz-Lopez; Anoop S. Mahajan; Feiyue Wang; Ana Borrego-Sánchez; A. Ulises Acuña; Carlos A. Cuevas; Juan Z. Dávalos; Aryeh Feinberg; Andrea Spolaor; Manuel F. Ruiz-López; Joseph S. Francisco; et al. (Proceedings of the National Academy of Sciences, 2025)
In the polar regions, which are vulnerable receptors of mercury pollution, atmospheric mercury depletion events (AMDEs) efficiently convert elemental mercury (Hg(0)) into oxidized mercury (Hg(II)) via bromine oxidation. Hg(II) subsequently deposits onto snow and sea ice. While field observations have shown that a large percentage of deposited mercury is re-emitted from the ice to the atmosphere by a photoinduced process, the fundamental photochemistry that drives the re-emission process remains unknown. Here, using multiconfigurational quantum chemistry, we find that the photoreduction of HgBr 2 , HgBr 3 − , and HgBr 4 2− in ice is more efficient than in the gas phase. This results from the influence of water molecules on the molecular geometry and electronic structure of mercuric bromides in ice, which enhances the absorption intensities at wavelengths relevant in the troposphere (λ > 290 nm), as compared to gas phase. Kinetic modeling shows that ~30 to 60% of deposited mercury in AMDEs can be reemitted due to the photoreduction of mercuric bromides in ice, in agreement with field observations. Our results reveal a photoreduction mechanism of sunlight-induced excited state chemistry of mercuric bromides on ice. These findings strongly suggest that this chemistry should be incorporated into atmospheric models to account for ice-atmosphere mercury cycling in the polar environments, currently not considered.